Freeze–thaw resistance of concrete produced with fine recycled concrete aggregates. (1st March 2016) - Bogas, J. Alexandre; de Brito, J.; Ramos, Duarte
Abstract: This paper's aim is to characterize the freeze–thaw resistance of normal strength and high-strength concrete with partial or total replacement of fine natural aggregate (FNA) by fine recycled concrete aggregate (FRCA). The surface scaling, mass loss, length change, residual ultrasound pulse velocity and residual compressive strength were monitored for different FRCA replacement ratios (0%, 20%, 50% and 100%) subjected to 300 freeze–thaw cycles according to ASTM C666 – Proc. A. In general, the mechanical strength decreases with the incorporation of FRCA, especially in high-strength concrete. Contrary to high-strength concrete, normal strength concrete was not frost resistant, regardless the type of aggregate used. The w/c ratio had a greater influence on the freeze–thaw resistance than the type of aggregate. The air entraining had a slightly beneficial effect on high-strength concrete. Generally, it is concluded that the incorporation of FRCA is not detrimental to the freeze–thaw resistance of concrete. Only the total replacement of FNA by FRCA led to lower residual mechanical strengths after freeze–thaw action than those obtained in reference mixes. However, surface scaling tends to be more severe in concrete with FRCA if it can be saturated near the concrete surface. Highlights: Concrete with different fine recycled concrete aggregates (FRCA) replacement ratios. Freeze–thaw resistance of normal strength and high-strength concrete with FRCA. Freeze–thaw resistance was more affected by the w/c than by the type of aggregate. FRCA was non-detrimental to freeze–thaw internal cracking resistance of concrete. Surface scaling was more severe in concrete with FRCA.